TEACHING RUSSIAN TO NON-PHILOLOGISTS: CURRENT STATE AND DEVELOPMENT STRATEGIES (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
Russian education in China has experienced more than 70 years of development, and its development results are closely linked to the relations between China and Russia. Russian education in the new era is showing a vigorous development trend, and it has also provided strong support for cultural exchanges and cooperation between China and Russia. However, at present, the College Russian education in Chinese universities has not received sufficient attention. Conduct research on the major universities in China that offer College Russian courses, sort out the basic status quo of College Russian education in Chinese universities, analyze the problems in their development process, and put forward reasonable suggestions and development strategies aimed at promoting the improvement of the quality of College Russian teaching and promoting the development of Russian education reform.
Keywords: Russian for non-philologists, Russian as foreign language, language level exam.